Pilot run of the new DAQ of the COMPASS experiment. Issue 8 (December 2015) - Novy, J; Bodlak, M; Jary, V; Konorov, I; Virius, M; Steffen, D; Tomsa, J; Kveton, A; Levit, D; Huber, S; Frolov, V
Abstract: This contribution focuses on the deployment and first results of the new data acquisition system (DAQ) of the COMPASS experiment at CERN laboratory. The COMPASS experiment is a fixed target experiment with maximum rate of 1.5 GB/s. The DAQ utilizing FPGA-based event builder is designed to be able to readout data at maximum rate of the experiment. The DAQ is developed under name RCCARS (run control, configuration, and readout system). The RCCARS has been deployed for the pilot run starting from the September 2014 and further developed for long run in 2015. In the paper, we present performance and stability results of the new DAQ architecture; we compare it with the original system in more details.